2001
DOI: 10.1002/1521-396x(200109)187:1<297::aid-pssa297>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of Zirconia-Coated Alumina as Support for Pt Particles

Abstract: ZrO 2 /Al 2 O 3 samples were prepared by impregnation of the alumina powder with a solution of zirconium hydroxide in nitric acid, containing ZrO 2 in the range of 1-20 wt%. Platinum was impregnated by incipient wetness technique, using an aqueous solution of H 2 PtCl 6 . The surface coverage of zirconia on alumina, as probed by XPS and ISS, increased up to 10 wt% of ZrO 2 and above this concentration crystallites of zirconia nucleated, which decreases the BET surface area. XRD measurements indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The values presented in this work are 0.6 eV smaller than that reported in the literature, which could indicate a change in the coordination number of zirconium due to the interactions with the other elements. Furthermore, XPS analyses of Pt/Zr system obtained by Souza et al [22] indicated similar behavior. These authors considered that it was only a surface phenomenon, restricted to the first atomic layer in the platinum neighboring.…”
Section: Xps Resultsmentioning
confidence: 99%
“…The values presented in this work are 0.6 eV smaller than that reported in the literature, which could indicate a change in the coordination number of zirconium due to the interactions with the other elements. Furthermore, XPS analyses of Pt/Zr system obtained by Souza et al [22] indicated similar behavior. These authors considered that it was only a surface phenomenon, restricted to the first atomic layer in the platinum neighboring.…”
Section: Xps Resultsmentioning
confidence: 99%
“…Similarly, there are different precursors that can be used in the formation of zirconia coating 88,[95][96][97][98][99] . The alkoxide form is still the popular choice, and zirconium propoxide and butoxide are among the commonly used 95,100 .…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…For catalysts that kinetically inhibit excessive carbon deposition, like zirconia-containing catalysts described here, the surface concentration of carbon at the metal surface (in the form of CH x ) is at steady state and remains constant, i.e., the rate of CH x decomposition equals that for CH x reaction with CO 2 adsorbed species. Assuming two independent balances of sites, the reaction rate of methane was derived and presented good correlation with the experimental results [38].…”
Section: Iss and Ftir ''In Situ'' Of Methane Reformingmentioning
confidence: 99%
“…The spectra showed a small band at 2178 cm À1 at 298 K, which was attributed to the linear adsorbed CO species on cationic sites (either Zr 4+ or Zr 3+ ). This adsorption involves the sdonation type to coordenatively unsatured surface cationic sites (cus), acting as Lewis acid centers, according to previous works [38]. The Pt/ZrO 2 catalyst reduced at 773 K showed also an intense band at 2130 cm À1 , which can be associated to CO adsorption on Pt-ZrO 2 interface, that means, on Pt sites interacting strongly with zirconia.…”
Section: Iss and Ftir ''In Situ'' Of Methane Reformingmentioning
confidence: 99%
See 1 more Smart Citation